Pengaruh Dividen, Return on Equity Dan Return on Asset Terhadap Harga Saham Manufaktur Di BEI - Yomina Siregar; Hermaya Ompusunggu (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The stock prices of manufacturing industry companies have decreased on average over the last 5 years, namely from 2016-2020. By -2%, a decrease in dividend stock prices, ROA and ROE. So this study aims to determine the relationship between dividends, ROE and ROA on stock prices. The method used in this study is quantitative with the type of secondary data in the form of documentation. The type of study population is Accessible Population or the available population is 37 manufacturing companies listed on the IDX in the last 5 years from 2016 to 2020, the sample in this study is 6 companies, the tests are descriptive statistics, classical assumptions, multiple linear regression and hypothesis testing using SPSS 16. The results partially show that dividends have a significant effect on stock prices, while ROA and ROE have no significant effect, simultaneously Dividends, ROA and ROE have a significant effect on prices. The conclusion in this study H1 is accepted, H2 is rejected, H3 is rejected and H4 is accepted.